Konstruktionen zwischen Lexikon und Grammatik (Linguistik – Impulse & Tendenzen, 2022)
The object of study in this edited volume is semi-schematic phrasemes, which are known in German construction grammar research by the term "phraseme constructions." Ten contributions by internationally renowned authors from the fields of construction grammar carry out a corpus-based study of various German phraseme constructions, contrasting them with five other European languages.